Bear in a square - Blackstone, Stella (Bristol, UK : Barefoot Books, 1998)
Squares, hearts, circles, and other shapes are hidden in the illustrations.
"A Barefoot beginner"--P. [4] of cover.
NP
Keywords: Form perception; Geometry; Shape